Embracing Generative AI in Education: Exploring Teachers' Perceptions, Practices, and Potential Impact - Echave, Jimson Ananayo; Donato, Vicelyn Joy Par; Acosta, Ofelia Damong (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
This research investigated how AI technologies can change education, focusing on personalized experiences, adaptive systems, and integrating AI tools in teaching practices. A mixed-method research design was applied, using both surveys and interviews to gain data from teachers concerning their views on generative artificial intelligence (AI) and its implications for their teaching practice. The study concludes that there is a range of teachers' familiarity with generative AI, indicating an optimistic perspective despite challenges such as training gaps and technological barriers. This report reveals that the successful implementation of AI technology in their work demands support and constant professional development programs. Age-related discrepancies were uncovered among the respondents, necessitating specialized training to handle different requirements across various ages. Inclusion in educational environments requires collaboration among teachers, policymakers, and artificial intelligence developers. It is recommended that future studies should include longitudinal impact assessment, comparative analysis of AI tools, cross-cultural exploration of AI adoption, investment in infrastructure policies that might promote the use of ICTs in education as well as development policies relating to technology yet this work adds to the existing literature on AI integration by providing insights for educators, policymakers, researchers who want to leverage the potentials of generative artificial intelligence (AI) technologies for improved teaching-learning process.